Evaluation of the ECOSSE model for simulating soil organic carbon under Miscanthus and short rotation coppice‐willow crops in Britain. Issue 4 (3rd November 2015) - Dondini, Marta; Richards, Mark; Pogson, Mark; Jones, Edward O.; Rowe, Rebecca L.; Keith, Aidan M.; McNamara, Niall P.; Smith, Joanne U.; Smith, Pete
Abstract: In this paper, we focus on the impact on soil organic carbon (SOC) of two dedicated energy crops: perennial grass Miscanthus x Giganteus ( Miscanthus ) and short rotation coppice (SRC)‐willow. The amount of SOC sequestered in the soil is a function of site‐specific factors including soil texture, management practices, initial SOC levels and climate; for these reasons, both losses and gains in SOC were observed in previous Miscanthus and SRC‐willow studies. The ECOSSE model was developed to simulate soil C dynamics and greenhouse gas emissions in mineral and organic soils. The performance of ECOSSE has already been tested at site level to simulate the impacts of land‐use change to short rotation forestry (SRF) on SOC. However, it has not been extensively evaluated under other bioenergy plantations, such as Miscanthus and SRC‐willow. Twenty‐nine locations in the United Kingdom, comprising 19 paired transitions to SRC‐willow and 20 paired transitions to Miscanthus, were selected to evaluate the performance of ECOSSE in predicting SOC and SOC change from conventional systems (arable and grassland) to these selected bioenergy crops. The results of the present work revealed a strong correlation between modelled and measured SOC and SOC change after transition to Miscanthus and SRC‐willow plantations, at two soil depths (0–30 and 0–100 cm), as well as the absence of significant bias in the model. Moreover, model error was within (i.e. not significantly larger than) the measurement error. The high degrees of association and coincidence with measured SOC under Miscanthus and SRC‐willow plantations in the United Kingdom, provide confidence in using this process‐based model for quantitatively predicting the impacts of future land use on SOC, at site level as well as at national level.